Harlequin ichthyosis—a case presentation. (29th September 2015) - Vrajananda, KY; Padmakumar, B; Judge, M; Moss, C
Abstract : Harlequin ichthyosis is the most severe form of congenital ichthyosis. In the past, the disorder was invariably fatal due to dehydration, infection, restricted respiration due to the plating, or other related causes and sufferers rarely survived for more than a few days. The authors describe the successful management of a baby with Harlequin ichthyosis. A male infant born to consanguineous parents at 35+2 weeks gestation had thickened skin with shiny plaques and deep, erythematous fissures. He had severe ectropion with red, swollen eyelids, small, rudimentary pinnae, nasal hypoplasia and a fixed, wide mouth. The limbs were encased in thick, hyperkeratotic skin with swollen extremities. A clinical diagnosis of Harlequin ichthyosis was made. He was started on regular topical treatment of emollients to the skin every 2–3 h, simple eye ointment to the eyes and oral acitretin. The Harlequin skin gradually started to shed, leaving normal looking skin underneath. He was bottle fed from day 1. The weight gain was poor initially. It improved with high-calorie feed supplementation. He developed staphylococcal and pseudomonas eye infection treated with topical antibiotics. He was discharged home at 4 weeks of age. He has continued to make good progress with a relatively normal-looking skin and good limb function. The management of Harlequin ichthyosis has markedly improved recently most notably with the use of retinoids. Some patients have survived into adolescence and rarely to adulthood. Harlequin ichthyosis has now been linked to mutations in ABCA12 gene improving the chance of prenatal diagnosis.